Microwave-assisted hydrothermal synthesis of sulfonated TiO2-GO core–shell solid spheres as heterogeneous esterification mesoporous catalyst for biodiesel production - Soltani, Soroush; Khanian, Nasrin; Choong, Thomas Shean Yaw; Asim, Nilofar; Yue, Zhao (Elsevier, 2021)
In accordance with the need for green production, the aim of current research is to synthesize a highly recyclable mesoporous SO3H-GO@TiO2 catalyst possessing both Brönsted and Lewis acid sites for one-pot catalyzing the esterification of inexpensive acidic feedstocks namely palm fatty acid distillate (PFAD), containing free fatty acids (FFAs, >85 wt%) and a considerable amount of water (3 wt%). The mesoporous sulfonated GO@TiO2 catalyst was synthesized using a two-step hydrothermal microwave-assisted method featured by uniform dispersion of TiO2 nanoparticles inside the mesopore framework of GO and post-sulfonation treatment. The effect of different GO:Ti ratios (1:0.1, 1:0.3, 1:0.5, and 1:1) on textural properties were examined and therefore, the ratio of 1:1 was selected as the optimum ratio for further experiments. The mesoporous SO3H-GO@TiO2 catalyst was characterized using Raman spectroscopy, Brunauer–Emmett–Teller (BET), X-Ray diffraction (XRD), temperature-programmed desorption (TPD), thermogravimetric analysis (TGA), field emission scanning electron microscopy (FESEM), and energy dispersive X-ray (EDX), and the results revealed that the as-developed catalyst possessed desirable textural properties as well as strong acidity with a combination of both Brönsted and Lewis acid sites. Furthermore, the crystalline structure of the as-prepared mesoporous GO@TiO2 material remains unaltered after the post-sulfonation treatment. In addition, the synthesized mesoporous SO3H-GO@TiO2 catalyst showed high stability for ten consecutive esterification reactions without additional treatments.